The energy transition in Portugal: business strategies, policy and context shifts - Salavisa, I.; Sousa, C.; Calapez, T. (22nd International Sustainable Development Research Society Conference (ISDRS 2016), 2016)
Portugal is an interesting case study in energy transition, due to its successful and rapid move towards renewable energy. A new sector has been formed at the confluence of technological opportunities and strong policy incentives, with the creation of a large number of new technology-intensive firms and the entry of some major incumbents into the business. This paper focus on the strategies deployed by the firms, taking advantage of the evolution of technologies, scale economies and more favourable market conditions, while also facing policy shifts, macroeconomic constraints and uncertainty. With the Portuguese budgetary crisis, severe restrictions impacted the sector, combining the decrease of incentives with a substantial rise of uncertainty. However, favourable shifts have also been at work. In fact, technologies have become more cost-effective, albeit at a differential pace in the various technological areas. Innovation and market strategies have played a major role in the way companies have dealt with these contextual shifts. These strategies have had distinct degrees of success due, among other aspects, to the heterogeneity of technological areas within the renewable sector. In addition, other policies have affected the sector such as European anti-dumping measures. We adopt a framework that: a) addresses context shifts (domestic and European policy, operating in domains such as the development of technologies, business supportive schemes, R&D support, and fiscal and trade policy; world competition; public acceptance) and their impact on the companies’ strategies; b) takes into account the distinctive evolution path of the various renewable energy technologies; c) addresses the interplay between firms’ innovation and market strategies. The framework is applied to 60 Portuguese renewable energy technologies firms. Data were collected through detailed interviews, based on a semi-structured questionnaire, with the founders or CEOs, complemented with extensive documentary information. The analysis permitted to identify: 1) the existence of distinctive strategies according to dimensions such as the technological area or the company´s origin; 2) the adequate matches of innovation and market strategies; 3) the impact of perceived obstacles and opportunities on the companies’ strategies and achievements; 4) the evolution prospects. Conclusions draw on the Portuguese case aiming to contribute to the general debate on energy transition.